Human Resources and its Impact on ICT and Modern Management in Corporate Profitability - Baraa Shaalan Amir; Oday Lateef Mahmood; Laith Ali Zgair; Jaber Ali Zghair (International Forum of Researchers and Lecturers, 2025)
Human resources management is the essence of modern management because it performs functions and functions that enhance its position in the organization's organizational structure and make it a means of survival and sustainability in activity and success. The compensation equity approved by the Foundation contributes directly to raising the efficiency of workers. This confirms the validity of our hypothesis in research, and because the incentive system has an important role in activating human resources, because the presence of internal motivation and desire to work alone is not enough. In our research, we discussed the following points. A close relationship between human resource activation factors, despite the difference allowed by the system of effective incentives to enhance the worker's sense of belonging to the institution. Evaluation of staff performance contributes to determining the factors that must be used to activate staff performance. Rewards are the main variable that influences a worker's desire and drives him to work seriously and sincerely.